Oxylipin responses to fasting and insulin infusion in a large mammalian model of fasting-induced insulin resistance, the northern elephant seal - Wright, Dana N; Katundu, Kondwani GH; Viscarra, Jose A; Crocker, Daniel E; Newman, John W; La Frano, Michael R; Ortiz, Rudy M (American Journal of Physiology-Regulatory, Integrative and Comparative Physiology, 2021)
The prolonged, postweaning fast of northern elephant seal (Mirounga angustirostris) pups is characterized by a reliance on lipid metabolism and reversible, fasting-induced insulin resistance, providing a unique model to examine the effects of insulin on lipid metabolism. We have previously shown that acute insulin infusion induced a shift in fatty acid metabolism dependent on fasting duration. This study complements the previous study by examining the effects of fasting duration and insulin infusion on circulating levels of oxylipins, bioactive metabolites derived from the oxygenation of polyunsaturated fatty acids. Northern elephant seal pups were studied at two postweaning periods (n = 5/period): early fasting (1-2 wk postweaning; 127 ± 1 kg) and late fasting (6-7 wk postweaning; 93 ± 4 kg). Different cohorts of pups were weighed, sedated, and infused with 65 mU/kg of insulin. Plasma was collected prior to infusion (T0) and at 10, 30, 60, and 120 min postinfusion. A profile of ∼80 oxylipins was analyzed by UPLC-ESI-MS/MS. Nine oxylipins changed between early and late fasting and eight were altered in response to insulin infusion. Fasting decreased prostaglandin F2α (PGF2α) and increased 14,15-dihydroxyicosatrienoic acid (14,15-DiHETrE), 20-hydroxyeicosatetraenoic acid (20-HETE), and 4-hydroxy-docosahexaenoic acid (4-HDoHE) (P < 0.03) in T0 samples, whereas insulin infusion resulted in an inverse change in area-under-the-curve (AUC) levels in these same metabolites (P < 0.05). In addition, 12-12-hydroperoxyeicosatetraenoic acid (HpETE) and 12-HETE decreased with fasting and insulin infusion, respectively (P < 0.04). The oxylipins altered during fasting and in response to insulin infusion may contribute to the manifestation of insulin resistance and participate in the metabolic regulation of associated cellular processes.